The World's First Hydromagnetic Artificial Heart: A Revolutionary Innovation in Cardiovascular Medicine - Seyedhosseini , Dr. Mohammad (South Eastern European Journal of Public Health, 2025)
Heart failure remains a leading cause of morbidity and mortality globally, particularly among individuals with advanced forms of the disease. This study introduces a groundbreaking hydromagnetic artificial heart designed to address the major limitations of existing devices, such as mechanical durability, biocompatibility, and efficiency. By integrating hydromagnetic propulsion mechanisms, nano-coils, and advanced biocompatible materials, this device demonstrates enhanced cardiac output restoration, improved diastolic function, and reduced risks of thrombosis. Preclinical trials in large animal models have shown remarkable results in terms of hemodynamic stability and long-term durability, paving the way for future clinical trials and eventual translation to human patients. Heart failure remains one of the leading causes of morbidity and mortality globally, affecting millions of individuals, with a major clinical challenge being the lack of effective long-term treatment options. This article presents the development of a novel hydromagnetic artificial heart designed to address the limitations of conventional cardiac devices, leveraging advancements in magnetic field technology, bioengineering, and biocompatible materials. The proposed device integrates cutting-edge technology to optimize pulsatile flow, improve energy efficiency, reduce immune rejection, and provide a longer lifespan. Preclinical studies have demonstrated the device's ability to restore normal cardiac output and sustain function even in advanced heart failure cases, such as those affected by atherosclerosis. This study aims to contribute to the future of cardiovascular medicine by providing insights into how this hydromagnetic artificial heart can transform heart failure management and improve patient outcomes.